2015
DOI: 10.18646/2056.31.16-004
|View full text |Cite
|
Sign up to set email alerts
|

Towards Satisfying Distributors in Multilevel Marketing Companies

Abstract: This study examined the relevant factors which affect the satisfaction of distributors towards multilevel marketing (MLM) companies in Malaysia. Six factors were investigated, which includes: method to diffuse business opportunity, perceived quality of recruiting process, perceptions of products and services, up-line support, perceived quality of training program, as well as monthly income. Results of the multiple regression analysis demonstrated that the first four factors significantly affected distributors'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Previous study [11] found no relationship between Reward Scheme and Career Choice, but in our research, we managed to prove otherwise. This result indirectly supports the notion that those who are most satisfied with MLM Company hence staying longer in their career path are those who benefit from its reward scheme [12]. Meanwhile, Company Credibility has a positive and significant effect towards Career Choice (H3).…”
Section: Table 7 R-squaredsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous study [11] found no relationship between Reward Scheme and Career Choice, but in our research, we managed to prove otherwise. This result indirectly supports the notion that those who are most satisfied with MLM Company hence staying longer in their career path are those who benefit from its reward scheme [12]. Meanwhile, Company Credibility has a positive and significant effect towards Career Choice (H3).…”
Section: Table 7 R-squaredsupporting
confidence: 65%
“…They argued that skepticism and poor communication on the reward system were the explanations for the insignificant relationships. Other study [12], however, found that monthly income or reward influenced the distributors' satisfactions with MLM Company. In this research, we assumed the better the reward the higher the motivation to undertake Islamic MLM as a career choice.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The highlight of this research was that it did not examine the leadership dimension for improving trust, however it was made very comprehensive as the reputation of network marketing is damaged by the practice of pyramid (Ivashkova et al, 2018;Koroth, 2012;Lee & Loi, 2016;Reingewerts, 2016) and Ponzi schemes (Lee & Loi, 2016) that are more inclined to fraudulent practices.…”
Section: Resultsmentioning
confidence: 99%
“…Trust is an assessment of confidence on another (a person, group, organization or system) based on positive expectations of future behavior (Hurley et al, 2013), trust is a process and individuals´ interaction between each other is an exchange process (Häkkinen, 2012). Trust is important and crucial (Lee & Loi, 2016) because of a strong desire to understand how to create effective cooperation in organizations. Trust is the key because it allows collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…Members in network marketing relationships employ a structured method of achieving gains (Bowen and Jones 1986). As noted from the research carried out by Lee and Loi (2016), several factors that affect network distributor satisfaction were explored, focusing on the diffusion of business ideas, perceived quality of members joining a network, training, support, perception of marketing offers, and the rewards every month to assess the strategies which are helpful in MML.…”
Section: Introductionmentioning
confidence: 99%